Comparison of different grafting techniques in open wedge high tibial osteotomy in terms of bone healing and functional outcomes (Annals of Medical Research, 2021)
None
Keywords: Knee; Osteotomy; Open Wedge; Tibia; Grafting; Bone Union.br /